Comparative Juridical Analysis of Consumer–Business Dispute Resolution Effectiveness: A Study of the Consumer Dispute Settlement Agency and the Court Mechanism - Kurniawan, Alvin; Setiadi, Edwin; Leonardo, Leonardo (LOCUS MEDIA PUBLISHING, 2025)
Consumer problem solving in business aspects can be solved in two ways, namely through the mechanism at BPSK and the Court. Problem solving through BPSK takes a mediation approach and prioritizes good faith and voluntariness. Efforts to resolve problems through the Court prioritize the mediation process first, if peace is not achieved, it will be continued to the trial process and the issuance of a decision from the trial, the power of the court's decision has strong legal authority. So in this study, it is worth examining the comparison of the effectiveness of resolving consumer problems through BPSK and the Court. This research is a normative legal research, legal research based on literacy materials in the form of books, journals, legal theories and laws and regulations that are developing in society and using a comparative concept approach by comparing or comparing one of the legal institutions.